Therapeutic Potential of Green Synthesized Zinc Oxide Nanoparticles Derived from Withania coagulans Extract against High-Fat Diet Associated Hyperlipidemia in Rat Model - Aman Ullah, Sayed; Hassan, Faiza; Khaliq, Jahanzaib; Ikram Ullah; Khan, Shakeel; Ahmed, Sageer; Nawab, Hina; Rashid, Aqsa; Arif, Amna; Saboor, Abdul (Indus Journal of Bioscience Research, 2025)
Background: Withania coagulans (Indian rennet, paneer phool, or rishyagandha) an herbal medicinal plant that belongs to the family Solanaceae, common English name ‘‘Indian Chees maker’’ and in Pashto called ‘‘Khamazora’’. Aim: the study was conducted to evaluate the anti-hyperlipidemic activity of “Withania coagulans”. Methodology: Total six groups of Wister rats (n=6) and each group with six replicates (r=6) were selected. Each group was labeled as control group, negative control group, Standard group, and Treatment group. Group 1st received normal routine feed with water, group 2nd received a high-fat diet of 30%, groups 3rd, 4th, 5th, and 6th were also fed with a high-fat diet and were treated with the standard anti-hyperlipidemic drug Atorvastatin(2.6mg), low dose (125mg), medium dose (250mg) and high dose (500mg) of W. coagulans plant extract using ZnO nanoparticles respectively. Zinc Oxide Nanoparticles (ZnO-NP) were characterized by Zeta size and Zeta potential. Over the course of the 49-day trial, which included 28 days for the induction of hyperlipidemia and 21 days for treatment, the rats were decapitated for the purpose of collecting samples, including blood and various organs, and serological tests were performed to assess the impact of W. coagulans. Results: A high dose of W. coagulans plant extract significantly decreased the elevated level of LDL-C, triglycerides, total cholesterol, ALT, AST, creatinine, and Urea, and significantly increased the low level of HDL-C, RBCs and WBCs count, and SOD. Conclusion: W. coagulans plant extract utilizing ZnO-NPs had a notable impact on these models of hyperlipidemic-induced rates.